Platelet mitochondria, a potent immune mediator in neurological diseases - Ma, Yan; Jiang, Qian; Yang, Bingxin; Hu, Xiaoyu; Shen, Gang; Shen, Wei; Xu, Jing (Frontiers in Physiology, 2023)
Dysfunction of the immune response is regarded as a prominent feature of neurological diseases, including neurodegenerative diseases, malignant tumors, acute neurotraumatic insult, and cerebral ischemic/hemorrhagic diseases. Platelets play a fundamental role in normal hemostasis and thrombosis. Beyond those normal functions, platelets are hyperactivated and contribute crucially to inflammation and immune responses in the central nervous system (CNS). Mitochondria are pivotal organelles in platelets and are responsible for generating most of the ATP that is used for platelet activation and aggregation (clumping). Notably, platelet mitochondria show marked morphological and functional alterations under heightened inflammatory/oxidative stimulation. Mitochondrial dysfunction not only leads to platelet damage and apoptosis but also further aggravates immune responses. Improving mitochondrial function is hopefully an effective strategy for treating neurological diseases. In this review, the authors discuss the immunomodulatory roles of platelet-derived mitochondria (PLT-mitos) in neurological diseases and summarize the neuroprotective effects of platelet mitochondria transplantation.